Beyond the fantastic crítica de arte contemporánea desde América Latina - Mosquera, Gerardo 1945- (Universidad de Granada, 2022)
This anthology, edited by Cuban art historian and critic Gerardo Mosquera, offers a wide selection of writings by some of the most important cultural theoreticians of contemporary Latin America. Together they comprise a distinctive corpus of new theoretical discourses, critical of modernity and solidly and pragmatically anti-utopian. The collection balances traditional and popular aesthetic-symbolic production as well as Afro- and Indo-American presences in the visual arts, and covers the whole of the Americans, including the Caribbean and the United States
Keywords: Ästhetik; Kunstkritik; Kunst; Lateinamerika; Aufsatzsammlung